Application of the gold ring bundles for innovative non-redundant sonar systems - Riznyk, V.; Bandyrska, O.; Skrybaylo-Leskiv, D. (Archives of Acoustics, 2006)
The paper involves techniques for configure linear, planar or three-dimensional spacetaperedarrays of radar or sonar system, using novel designs based on the Perfect CombinatorialSequencing Theory, namely the concept of Gold Ring Bundles (GRB)s for findingthe optimal placement of array antenna elements in the system with respect to minimizingside lobes, while maintaining or improving on resolving ability and the other significant operatingcharacteristics of the system. It is shown that the method provides many opportunities ofthe concept for configure of non-uniform array with non-redundant aperture of array systems,including acoustics and hydroacoustics.